Republic of Moldova : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The economic growth of Moldova continued to be strong during the Economic Growth and Poverty Reduction Strategy Paper (EGPRSP) implementation period despite external shocks. Macroeconomic management remained prudent in reducing public external debt. The government has approved National Development Strategy (NSD) (PRSP II), which aims to unify the reduction strategy and development vision. The Joint Staff Advisory Note (JSAN) emphasized the need for strengthening strategy and its effective implementation. It also stressed the need to maintain a macroeconomic framework, ensure better strategic linkages between annual budgets, medium-term expenditure framework (MTEF) and Poverty Reduction Strategy Paper (PRSP), restructuring of public finances, and strengthening the target efficiency of social assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet